The Acceptance of Wayang Kamasan Porcelain Ceramics at Petitenget Temple Bali - Rai, Sunarini; I Wayan, Mudra; Anak Agung Ayu Oka, Saraswati; I Ketut, Muka; I Wayan, Karja (Mudra Jurnal Seni Budaya, 2024)
Temples, integral to Hindu Dharma worship, are quintessential features of Balinese architectural tradition. Among these, Petitenget Temple stands out with its distinctive interior, adorned with ceramic plates embellishing the pelinggih (shrine). This study focuses on Petitenget Temple, where porcelain ceramic plates featuring the Wayang Kamasan motif are utilized within the Tri Angga framework, representing a novel exploration. Research related to the study of the use of porcelain ceramics as ornaments in old buildings in Bali. Previous research has been carried out but has not been studied in depth on the use of Wayang Kamasan motifs on pelinggih with the Tri Angga concept in particular. This research aims to reveal the form, meaning, and aesthetic value of porcelain ceramics with wayang kamasan motifs as ornaments on pelinggih. Using qualitative methods with a descriptive approach, data collection involved observation, in-depth interviews, and documentation, and data reduction flow. Meanwhile, the data source sampling technique uses purposive sampling. The findings obtained through analysis of the Wayang Kamasan motif applied to porcelain ceramic plates at Petitenget Temple, Kerobokan Badung, are the harmony of Wayang motif porcelain ceramics, as a prototype or reference for preserving the use of Wayang Kamasan motif porcelain ceramics in sacred buildings and other functions, and temple visitors can enjoy the form, meaning, and aesthetics displayed by the porcelain ceramics with Wayang Kamasan motifs installed. From this research, it can be concluded that Wayang Kamasan porcelain ceramics are accepted by the community, temple owners, or Petitenget Temple owners.